Determination of the phenology of Aloysia citriodora (Palau) and the associated arthropods (2024)
Lemon verbena, Aloysia citriodora (Palau) has been widely used in traditional medicine, cosmetics, and the food industry. In Colombia the foliage is marketed fresh but there is no information regarding the plant phenology, nor on the insects associated, therefore the management practices are still empirical, and sometimes does not comply with the national regulations for the commercialization of medicinal plants. In this study it was determined that it takes 32 weeks from planting to flower senescence completing its phenological cycle; likewise, an associated arthropofauna of 50 families with different feeding habits were found, suggesting that the species offers different ecosystem services. The information obtained could contribute to establish more effective management plans for arthropods, and to improve quality of materials with medicinal purposes.